2022
DOI: 10.3389/fvets.2022.908862
|View full text |Cite
|
Sign up to set email alerts
|

Breast Meat Fatty Acid Profiling and Proteomic Analysis of Beijing-You Chicken During the Laying Period

Abstract: The disparity in fatty acids (FA) composition exhibits a significant impact on meat quality, however, the molecular regulatory mechanisms underlying this trait in chicken are far from clear. In this study, a total of 45 female Beijing-You chicken (BYC) hens, fed on the same diet, were collected at the slaughter age of 150, 300, or 450 days (D150, D300, and D450) from sexual maturation stage to culling stage (15 birds per age). Gas chromatography-mass spectrometry (GC-MS) and tandem mass tag labeling technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…In nestlings from the enlarged broods, methylation of this site decreased with hatch date. High FOXC1 expression is associated with a low percentage of abdominal fat in chickens (Sun et al, 2013) and dynamic expression of GMDS has been found in during the laying period in chicken breast muscle (Zhang et al, 2022). Therefore, methylation of this CpG might regulate or reflect nestling condition, especially since nestling weight also decreased with hatch date in the enlarged broods in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In nestlings from the enlarged broods, methylation of this site decreased with hatch date. High FOXC1 expression is associated with a low percentage of abdominal fat in chickens (Sun et al, 2013) and dynamic expression of GMDS has been found in during the laying period in chicken breast muscle (Zhang et al, 2022). Therefore, methylation of this CpG might regulate or reflect nestling condition, especially since nestling weight also decreased with hatch date in the enlarged broods in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The light-absorbing capacity of the eggshell is related to the shell's color, strength and thickness. Generally, brown eggs have larger shell thickness, on average 0.37 mm [24], while the light-pink shells have an average thickness of 0.32 mm in the intermediate period of egg laying, which affects the light absorption capacity [25].…”
Section: Discussionmentioning
confidence: 99%
“…ACSBG2, which catalyzes the conversion of long-chain FAs to their active form acyl-CoAs for both lipid synthesis and beta-oxidation, was identified as a key gene involved in the adipogenic differentiation of chicken preadipocytes [49]. Furthermore, in laying hens of different ages, HADH, ACAA2, HADHA, and ACSL1 were differentially expressed proteins associated with a disparity in FA compositions [50].…”
Section: Discussionmentioning
confidence: 99%